Usefulness of Thrombin Generation - Tripodi, Armando (Hämostaseologie, 2020)
Thrombin generation (TG) is a global coagulation procedure meant to continuously monitor thrombin formation and decay upon exposure of platelet-poor plasma to exogenous triggers such as tissue factor, phospholipids, and calcium chloride. The procedure can also be performed in platelet-rich plasma by omitting exogenous phospholipids. TG is thought to mimic more than other coagulation procedures the process that occurs in vivo. Over the years, TG has been used to investigate coagulation mechanisms, which were not completely understood, or to investigate hyper- or hypocoagulability in clinical conditions known to be at increased risk of thrombosis or hemorrhage, respectively. More recently, TG has been employed as a laboratory tool to assess the risk of recurrent venous thromboembolism or to assess the risk of arterial thromboembolism in specific clinical settings or in the general population. The article reviews the value and limitations of TG.
Keywords: arterial thrombosis; coagulation factors; Hemostasis